"Cutty Shark" i hvalfangsten tjeneste - Berg, Knut (Årbok. Sandefjord bymuseum, 1969)
Publisher: Sandefjord bymuseum Place: Sandefjord
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

Svalbard, Jan Mayen, antarktische Besitzungen - Gjelsvik, Tore (1969)
Publisher: Utenriksdepartementet Place: Oslo
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

Ny amerikansk forskningsstasjon på Sydpolen vil bli oppkalt etter polfarerne Amundsen og Scott - Grossman, Joseph (Polarposten, 1969)
Keywords: Antarktis; stasjoner

Glaciology and glacial geology on Deception Island - Kläy, Jean-Roland; Orheim, Olav (Antarctic Journal of the United States, 1969)
Keywords: Antarktis; geologi; glasiologi

"Forlandet" ex "Femern" ex "Foca" - Knap, Johan (Årbok. Sandefjord bymuseum, 1969)
Publisher: Sandefjord bymuseum Place: Sandefjord
Keywords: Sørishavet; historie; hvalbåter; hvalfangere; hvalfangstindustri; hvalindustri; pelagisk; skip

Amerikanske kvinnelige vitenskapsmenn studerer pingviner i Antarktis - Schroth, Charles (Polarposten, 1969)
Keywords: Antarktis; forskning

Arctic and Antarctic : current problems in the Polar region - Sollie, Finn (Cooperation and Conflict, 1969)
Keywords: Antarktis; Antarktistraktaten; internasjonal; politikk; rett

Arctic and Antarctic : current problems in the Polar region - Sollie, Finn (Cooperation and Conflict, 1969)
Sætrykk
Keywords: Antarktis; Antarktistraktaten; polarområdene; politikk; utforskning; vitenskap

Norwegian Antarctic Expedition, 1968-69 - Winsnes, Thore S. (Antarctic Journal of the United States, 1969)
The aim of the Norwegian Antarctic Expedition was to carry out mapping, geological and glaciological investigations of the Kraul Mts. in western Queen Maud Land. The expedition received the assistance of the National Science Foundation in the provision of American equipment and arrangements for logistics. The six member expedition, equipped for 2 1/2 months of field operations was taken by LC-130 Hercules aircraft from McMurdo to the Kraul Mts. where on several sledge journeys, covering 800 km in all, the geology of the mountains was mapped, triangulations made and base measurements taken during Nov. 22, 1968 to Jan. 20, 1969. The geology of the Kraul Mts. is rather monotonous, consisting of amygdaloid basic-to-intermediate lavas in thick, nearly flat-lying beds. An ultrabasic olivine-rich intrusive is dominant in the westernmost part of the mountains. In the east, a small isolated outcrop con sisted of sedimentary rocks in a sequence of about 50 m, containing a fossil Glossopteris flora of Permian Age. All mountains were crossed by dolerite sills and dykes. During work in the mountains, animal and plant life were observed, and some samples were taken. Core drillings were taken at the ice shelf 70 km to the N, for comparison with main basic cores.
Coordinates: S731959 S731959 W0141000 W0141000
Keywords: Dronning Maud Land; Norwegian Antarctic Expedition 1968-69; geodesi; geologi; glasiologi; kartlegging; topografi